Strategic pathways to product innovation capabilities in SMEs - Branzei, Oana; Vertinsky, Ilan (Journal of Business Venturing, 2006)
The study articulates a two-dimensional typology of dynamic capabilities, grouping them by the life-cycle stage and the timing of expected returns. Using a cross-industry sample of manufacturing SMEs, we validate and map four distinct innovation strategies onto specific sets of product innovation capabilities. Results show that human capital development efforts catalyze both the external absorption and the internal emergence of novel capabilities. Stronger emphasis on product features and broader market access stimulate the effective replication of extant capabilities, yielding immediate payoffs. Process-focused strategies are a double-edged sword: they facilitate the acquisition and incorporation of external insights yet bound internal capability development.